EVALUATION OF HEPATOPROTECTIVE POTENTIALS OF METHANOL EXTRACT OF TEPHROSIA VILLOSA AGAINST THIOACETAMIDE INDUCED LIVER TOXICITY IN ALBINO RATS - RAWAL, PINKEY; C, RAMESH; PRAMANIK, SOMA; S, SHABANA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present study was conducted to determine the hepatoprotective potentials of methanol s extracts of Tephrosia villosa leaves against thioacetamide (TAA) induced liver damage in rats. Methodology: The acute oral toxicity study was conducted as per OECD guidelines, and the extract was proved to be safe up to the dose of 2000 mg/kg. The total duration of the study was 21 days, and animals were divided into six groups. Hepatotoxicity was induced in the animals of all groups except normal control by single dose administration of TAA (100 mg/kg) at 1st day of the study followed by animals were treated daily with standard drug silymarin and methanol extract of T. villosa (100 mg/kg, 200 mg/kg and 400 mg/kg) to respective groups for 21 days. Variations in biochemical parameters such as alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bilirubin, direct bilirubin, albumin, total protein, ions and others parameters such as clotting time and weight of the liver were considered to determine beneficial effect of the extract. At the end of the study liver samples were collected and subjected to histopathological evaluation. Results: In control animals treated with TAA alone, there were variations in the above mentioned parameters. However in the animals treated with methanol extract and standard drug silymarin, all the parameters were normal possibly due to their beneficial property in protecting the liver against TAA induced hepatotoxicity. Conclusion: The results obtained in the above study suggesting that, the methanol extract of T. villosa possess significant hepatoprotective activity.